Discretionary Access Controls for a Collaborative Virtual Environment - Wright, Timothy; Madey, Greg (International Journal of Virtual Reality, 2010)
As collaborative virtual environments (CVEs) are more widely used, participant access to CVE objects and information becomes a significant concern. In virtual reality games, storefronts, classrooms, and laboratories, for example, the need to control access to spaces and objects is integral to the security of activities taking place there. However, limited access controls are typically available in CVEs. Often, such controls are course-grained, only protecting against movements by unauthorized participants into specific areas. In answer to this deficiency, we offer a discretionary access control (DAC) system based on traditional concepts of users and groups, and tailored to the needs of a CVE. Our system, called WonderDAC, includes the ability to restrict movement into areas, as well as control interactions with objects. A basic WonderDAC prototype has been implemented within the Project Wonderland CVE.